Challenges inmates face in utilizing human immunodeficiency virus testing services and accessing antiretroviral therapy at Maula prison in Lilongwe district. - Jowasi, Ignasio Mathews (Kamuzu University of Health Sciences, 2022)
BACKGROUND HIV infection in prisons is higher than in the general population (AVERT, May 2010). According to latest figures for Maula Prison, the authorities reported that 40% of its population is reactive unlike the average prevalence rate of 12% nationwide. This study would like to explore the challenges these inmates face in accessing HCT services and ARVs. SIGNIFICANCE This study will be used as an evaluation tool in HCT and ARV administration in prisons. Healthy prisoners positively contribute to the work force of the prisons' farms. The government will reduce the cost of food for the prisoners. Proper referral system of pardoned or acquitted prisoners can bee established. METHODOLOGY The research design will be a qualitative study design in order to get more of the participants' interpretation of the situation. An interview guide containing both open and close ended questions will be used for data collection. Purposive or judgmental sampling will be used in this study from a population of 10 prisoners at Maula prison in Lilongwe District. ETHICS Permission will be requested for from relevant authorities for approval before going ahead with data collection. KCN Research and Publications Committee, Prison Headquarters, Maula prison and Ntchisi prison will be approached for their approval. Participants will be explained on being involved in the study on voluntary basis and can drop at any time without being penalized. Finally, the participants will be given a consent form to sign before data collection to show that they have accepted to take part in the study.